2014
DOI: 10.1186/1471-2458-14-57
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of family mediation and the role of family violence: study protocol

Abstract: BackgroundFamily law reforms in Australia require separated parents in dispute to attempt mandatory family dispute resolution (FDR) in community-based family services before court attendance. However, there are concerns about such services when clients present with a history of high conflict and family violence. This study protocol describes a longitudinal study of couples presenting for family mediation services. The study aims to describe the profile of family mediation clients, including type of family viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…In the United Kingdom, for example, Trinder, Firth, and Jenks (2010) found that mediators marginalized allegations of violence and responded punitively when women were persistent in raising issues that affected children's safety. The introduction of mediation as a core element of the new policy lacked an evidence base about the impact of mandating mediation to a client group in which high rates of domestic violence could be anticipated but may not be readily identified (Cleak, Schofield, & Bickerdike, 2014).…”
Section: The Policy Contextmentioning
confidence: 99%
“…In the United Kingdom, for example, Trinder, Firth, and Jenks (2010) found that mediators marginalized allegations of violence and responded punitively when women were persistent in raising issues that affected children's safety. The introduction of mediation as a core element of the new policy lacked an evidence base about the impact of mandating mediation to a client group in which high rates of domestic violence could be anticipated but may not be readily identified (Cleak, Schofield, & Bickerdike, 2014).…”
Section: The Policy Contextmentioning
confidence: 99%
“…This article is based on analysis of baseline data from a longitudinal project designed to evaluate the relationship between IPV and family mediation process and outcomes (Cleak, Schofield, & Bickerdike, 2014). Family mediation clients were recruited from nine FDR centers run by Relationships Australia Victoria (RAV), in both metropolitan and rural Victoria.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the fact that many families try to suppress or avoid conflict, it might lead to divorce (Aye, et al, 2016). Family disagreements can lead to parental disengagement and negatively impair children's cognitive competency via intensifying disruptive conduct (Cleak, Schofield, & Bickerdike, 2014). It can also lead to emotional, financial, and parental problems.…”
Section: A Background Of the Studymentioning
confidence: 99%
“…It can also lead to emotional, financial, and parental problems. Family disagreement, in severe circumstances, can lead to violence, causing physical, psychological, and social problems for family members, particularly children and parents (Cleak, Schofield, & Bickerdike, 2014). Both formal and informal strategies are effective in resolving family issues.…”
Section: A Background Of the Studymentioning
confidence: 99%
See 1 more Smart Citation